Global media flows: A qualitative review of research methods in audio-visual flow studies. (October 2019) - Iordache, Catalina; Van Audenhove, Leo; Loisen, Jan
Recent developments in the online distribution and consumption of audio-visual content have brought relevant changes to the transnational flow of content. Thus, the need for a theoretical and methodological rejuvenation of flows research has been signalled. The aim of the present study is to analyse the different flow studies throughout time, following a series of parameters such as research question, methodology and scale of study. This article is a systematic literature review of 30 flow studies on film and television programmes, published between 1974 and 2014. The methods used by the studies are brought into focus and discussed thoroughly, in light of the method of data collection, the type of data used and the method of data analysis. Main findings show an evolution towards more detailed research, to include more contextual factors, an increased use of secondary data, as well as more focused regional and comparative studies.